2022
DOI: 10.1016/j.eclinm.2022.101283
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anemia among people living with HIV: A systematic review and meta-analysis

Abstract: Background Anemia is the most frequent hematologic abnormality among people living with human immunodeficiency virus (HIV) (PLWHIV) and is associated with HIV disease progression and higher risk of mortality of the patients. However, there is a wide variation of the prevalence of anemia among PLWHIV in different clinical settings. We aimed to obtain more precise estimates of prevalence of anemia and severity of anemia among PLWHIV, which may be important for patients, caregivers, researchers and health policy-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 108 publications
2
39
1
3
Order By: Relevance
“…Several studies have documented anemia in HIV infected individuals indicated by significantly lower mean levels of RBC, Hb and PCV [24,1]. The most prevalent hematologic abnormality among HIV-positive individuals is anemia, which is also linked to the course of the disease and a higher mortality risk for the patients [42]. Patients with HIV experience anemia for a variety of reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have documented anemia in HIV infected individuals indicated by significantly lower mean levels of RBC, Hb and PCV [24,1]. The most prevalent hematologic abnormality among HIV-positive individuals is anemia, which is also linked to the course of the disease and a higher mortality risk for the patients [42]. Patients with HIV experience anemia for a variety of reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Macrocytic anemia is broadly classified as [1] megaloblastic associated with vitamin B12 and folate deficiency and [2] the nonmegaloblastic moiety associated with chronic alcoholism, liver disease, hypothyroidism, hereditary spherocytosis, and states of increased red cell consumption such as hemolysis or high turnover in pregnancy [21].…”
Section: Discussionmentioning
confidence: 99%
“…Anemia is a frequent hematological complication of human immunode ciency virus (HIV) infection, and its incidence is adversely associated with advanced HIV disease, poor treatment outcomes, and increased risk of patient mortality [1,2]. Although the causes of anemia in the general population are multifactorial in origin with various pathophysiological mechanisms, the most common etiology globally is iron de ciency, among other nutritional deciencies such as folic acid and vitamin B12 [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By univariate analysis, we detected a significant association between SARS-CoV-2 serology status and elevated (>1000 copies/mL) HIV VL (31.4% versus 14.6% uncontrolled HIV VL in SARS-CoV-2 seropositive versus seronegative patients, p = 0.04, Figure 2), sodium concentration (45.6% below normal range in SARS-CoV-2 seropositive (range 128-144 mmol/L) versus 27.9% in seronegative patients (range 134-143 mmol/L), p = 0.047), mean corpuscular hemoglobin as a measure for oxygen (8.7% versus 0% below normal range in SARS-CoV-2 seropositive versus seronegative patients, p = 0.048), monocyte count (0% versus 6.8% above normal range in SARS-CoV-2 seropositive versus seronegative patients, p = 0.029), CD45+ white cell count (0% versus 4.8% above normal range in SARS-CoV-2 seropositive versus seronegative patients, p = 0.041) and CD4 percentage of lymphocytes (96.1% versus 83.3% below normal range in SARS-CoV-2 seropositive versus seronegative patients, p = 0.014). Interestingly, in addition to uncontrolled HIV VL, hyponatremia and anemia are indicative of HIV disease severity [26,27], as well as of adverse COVID-19 disease outcome [5,13,28,29].…”
Section: Association Of Clinical Parameters With Sars-cov-2 Seroconve...mentioning
confidence: 99%